Analysis of Ability to Understand Concepts Using the Contextual Teaching and Leaning Learning Model in Class XI SMA Negeri 1 Ulu Idanotae - Winistina Giawa; Amin Otoni Harefa; Yulisman Zega (CV. Rayyan Dwi Bharata, 2023)
This research is based on the results of observations and interviews with teachers at SMA Negeri 1 Ulu Idanotae where researchers obtained information that the ability to understand students' concepts was low, making it difficult for students to explain math problems, this is evidenced by the average student test scores. only around 59 with sufficient category. This study aims to find out how students' understanding abilities when using the Contextual Teaching and Learning model. This type of research is quantitative research with a descriptive approach. The research design used is the One-Shot Case Study. The research instrument used was a test of the ability to understand mathematical concepts. The number of population in this study is 215 people with a large sample of 36 people taken using nonprobability sampling with purposive sampling technique. Based on the results of the research, after learning in class using the Contextual Teaching and Learning learning model, it was obtained that the average ability to understand students' mathematical concepts was 75.38 which was in the good category. This is inversely proportional to the average ability to understand students' mathematical concepts when making initial observations, which were only around 59 in the sufficient category. It can be shown that the mathematical understanding ability of students at SMA Negeri 1 Ulu Idanotae increased when learning was implemented using the Contextual Teaching and Learning model.